Does Consumer Ethnocentrism Matters on Brand Origin Recognition Accuracy (BORA) of Young Malay Muslims in Malaysia? - Poh-Chuin Teo, Ramayah Thurasamy, Theresa C. F. Ho (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In sustaining the research excellence of country of origin research, recent researchers have challenged the assumptions of this research topic and introduced a new direction namely Brand Origin Recognition Accuracy (BORA), which aims to examine the accuracy of consumers’ capability in recognizing brand’s origin country. Despite several studies have been carried out in BORA, the results remain inconsistent and provide further room for investigation. The objective of this research is to see how consumer ethnocentrism affects the abilities of young Malay Muslims to recognise domestic brands. A BORA matrix was developed based on the suggestions given by Samiee et al. in their seminal BORA research in 2015; and Consumer Ethnocentrism Scale (CETSCALE) used to capture consumer ethnocentrism. The SmartPLS findings of the study revealed that consumer ethnocentrism explained a large portion of respondents’ local BORA score. Research limitations and recommendations for future studies were discussed.